SOLAR AND WIND ENERGY MODELLING FOR CENTRAL BANGKA REGENCY, BANGKA BELITUNG PROVINCE - Wahyu Edifikar; Bertha Maya Sopha; Ahmad Agus Setiawan (Master in Systems Engineering, 2020)
Central Bangka is a developing regency in Bangka Belitung Island Province. Geographically Bangka Belitung Islands is not far from the equator. The development of human resources and infrastructure for the energy sector is an integral part of regional development efforts. To fulfill the district's energy, we need to look at the potential of renewable energy such as wind power and solar power within the district. This research also provides the potential renewable energy capacity configuration through a simulation.This research used the simulation approach method to map the energy demand over the district and renewable energy available in the region. Energy demand data received from the National Electrical Company (PLN) of Bangka Belitung Province, and potential renewable energy data were obtained from the Ministry of Energy and Mineral Resources of The Republic of Indonesia and the NASA website. Software HOMER is used to analyze electrical energy potential from renewable energy sources.The simulation shows wind energy could provide 0.15 – 0.19 kW and solar power at 3.99 – 4.96 kW/m2/day. The optimum configuration of energy supply consists of 61.4% solar energy and 38.6% wind energy. The hybrid configuration above using the solar photovoltaic (PV) output of 286,981 kWh/year and wind generator output of 180,758 kWh/year and an estimated value of 1,663,598.53 for capital cost, 134,548.34 of operational cost, and cost of energy generated at 0.43/kWh.